2010
DOI: 10.3109/00365599.2010.488246
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and health-related quality of life in patients with lower urinary tract symptoms suggestive of benign prostatic obstruction compared to the general population and patients with inguinal hernia

Abstract: Patients with LUTS suggestive of BPO had significantly impaired sleep, a higher prevalence of insomnia and significantly impaired HRQoL compared with one or both of the comparison groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…A study in Sweden investigated the effect of LUTS on sufferers’ sleep quality, and compared 239 men referred with LUTS, 213 men in the general population and 200 men scheduled for repair of inguinal hernia (all aged 45–80 years) . Men with LUTS had a higher prevalence of insomnia (40%) than the general population (26%) and hernia (19%) groups ( P < 0.001) and a greater proportion of men had poor sleep efficiency (defined as the ratio of reported nocturnal sleep duration and time spent in bed × 100; ≥ 85% is considered to be satisfactory) at 49% vs 39% and 31%, respectively, as assessed by the Uppsala Sleep Inventory.…”
Section: Resultsmentioning
confidence: 99%
“…A study in Sweden investigated the effect of LUTS on sufferers’ sleep quality, and compared 239 men referred with LUTS, 213 men in the general population and 200 men scheduled for repair of inguinal hernia (all aged 45–80 years) . Men with LUTS had a higher prevalence of insomnia (40%) than the general population (26%) and hernia (19%) groups ( P < 0.001) and a greater proportion of men had poor sleep efficiency (defined as the ratio of reported nocturnal sleep duration and time spent in bed × 100; ≥ 85% is considered to be satisfactory) at 49% vs 39% and 31%, respectively, as assessed by the Uppsala Sleep Inventory.…”
Section: Resultsmentioning
confidence: 99%
“…The medians and quartiles (Q 1 -Q 3 ) of the IPSS were 19 (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), the SPI 16 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), the BII 7 (3-9) and the bother question in the IPSS 3 (3)(4).…”
Section: Resultsmentioning
confidence: 99%
“…Although it is known that men with LUTS have impaired health-related and disease-specific quality of life [1][2][3][4], little is known about how the men's urinary problems affect the quality of life of their partners. In a population study, both men with an enlarged prostate and with moderate to severe LUTS symptoms and their partners experienced relationship strains such as lack of physical intimacy and lack of communication [5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to issues of sleep quality, an increased severity of nocturia positively correlates with poorer overall health status . Patients with LUTS/BPO are also reported to have a high prevalence of insomnia and impaired QoL …”
Section: Introductionmentioning
confidence: 99%
“…6 Patients with LUTS/BPO are also reported to have a high prevalence of insomnia and impaired QoL. 7 Some previous studies showed that alpha-adrenergic antagonist, the main medical treatment for patients with LUTS/BPO, significantly improved both nocturia and sleep disorders. 8,9 However, there are few reports focusing on whether TURP, a standard surgical procedure to relieve obstruction in patients with LUTS/BPO for many decades, can improve nocturia and sleep quality.…”
Section: Introductionmentioning
confidence: 99%